Professional Engagements and Teaching Approaches of Public Elementary School Teachers - Lariza, Myra LIta Esquillo (IDEAS: Journal of Management & Technology, 2025)
The study investigated the level of professional engagements and degree of teaching approaches of teachers in Roxas City District III. The respondents of the study were 188 randomly selected elementary school teachers in Roxas City District III. The study used the descriptive-correlational research design. Data were collected using a validated and reliability-tested researcher-made questionnaire. Statistical tools used to analyze and interpret data were frequency count, percentage, mean, t-test, and analysis of variance, and Pearson r. The results revealed that the level of professional engagements of teachers was highly engaged and their degree of teaching approaches was to a high extent. There was significant difference the level of professional engagements of teachers when they were grouped according to educational attainment, while there was no significant difference when grouped according to sex, age, and length of teaching experience. There was no significant difference in the degree of teaching approaches of teachers when they were grouped according to sex, age, educational attainment, and length of teaching experience. The professional engagements of teachers was found to be significantly associated with their teaching approaches.